(untitled) (Periphērica: Revista de Historia Social, Cultural, y Literaria, 2022)
In this third issue of Periphērica (2.1) we offer a wide range of critical approaches to cultural production from Latinoamérica and Iberia. As in our past issues, most of the works analyzed here are not defined by one cultural center, a single nation-state, but instead they inhabit the intervals of migration, exile, travel, adaptation, and cultural circulation in different spaces: Argentina and Paris, Cuba and Spain, Murcia and Havana, Mexico and Barcelona, Lisbon and Mexico.